2011
DOI: 10.1371/journal.pone.0029247
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection Halts the Relaxation of Protamine 2 among Rodents

Abstract: Sexual selection has been proposed as the driving force promoting the rapid evolutionary changes observed in some reproductive genes including protamines. We test this hypothesis in a group of rodents which show marked differences in the intensity of sexual selection. Levels of sperm competition were not associated with the evolutionary rates of protamine 1 but, contrary to expectations, were negatively related to the evolutionary rate of cleaved- and mature-protamine 2. Since both domains were found to be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…It is possible that the adaptive evolution of PKDREJ is a generalized phenomenon across rodents, but the high degree of conservation of a large portion of the gene makes it difficult to detect positive selection when very closely related species are compared (Anismova et al, 2001;Zhang et al, 2005). A similar pattern was observed in previous work analysing the evolution of protamine sequences in murids (Martín-Coello et al, 2009) and cricetids (Lüke et al, 2011). An alternative explanation could be that positive selection is limited to the cricetid clade.…”
Section: Adaptive Evolution Of Pkdrej In Rodentssupporting
confidence: 66%
See 3 more Smart Citations
“…It is possible that the adaptive evolution of PKDREJ is a generalized phenomenon across rodents, but the high degree of conservation of a large portion of the gene makes it difficult to detect positive selection when very closely related species are compared (Anismova et al, 2001;Zhang et al, 2005). A similar pattern was observed in previous work analysing the evolution of protamine sequences in murids (Martín-Coello et al, 2009) and cricetids (Lüke et al, 2011). An alternative explanation could be that positive selection is limited to the cricetid clade.…”
Section: Adaptive Evolution Of Pkdrej In Rodentssupporting
confidence: 66%
“…The evolutionary rate of Pkdrej for each species was then calculated by comparing dN and dS values from the root of the phylogeny to the terminal branch giving an v ratio from the root. In this way, the total accumulated selective pressures during the evolution of the Pkdrej gene are accounted for, which is more suitable for testing associations with phenotypic data as it reflects the entire phenotypic evolution from the common ancestor (Lüke et al, 2011;Montgomery et al, 2011). In addition, estimating the rate of evolution since the last common ancestor forces that all branches have the same length and therefore the analysis is not subject to temporal effects on v (Wolf et al, 2009).…”
Section: Evolutionary Rates and Levels Of Sperm Competitionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have found a positive relationship between sequence divergence of these genes and levels of sperm competition, and several such genes show evidence of positive selection in coding regions ( [17][18][19][20][21], but see [22,23]). However, a positive correlation between sequence divergence in the promoter region of protamine 2 and relative levels of sperm competition in house mice and their close relatives [24] suggests that regulatory changes may also contribute to species differences in sperm competitive ability.…”
Section: Introductionmentioning
confidence: 99%